2015
DOI: 10.1002/jmri.24921
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in intratumoral regions with rapid gadolinium washout correlates with estrogen receptor status and nodal metastasis

Abstract: Purpose To evaluate heterogeneity within tumor subregions or “habitats” via textural kinetic analysis on breast dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) for the classification of two clinical prognostic features; 1) estrogen receptor (ER)-positive from ER-negative tumors, and 2) tumors with four or more viable lymph node metastases after neoadjuvant chemotherapy from tumors without nodal metastases. Materials and Methods Two separate volumetric DCE-MRI datasets were obtained at 1.5T, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 46 publications
(53 reference statements)
1
40
0
Order By: Relevance
“…Present studies of intratumoral analyses mainly focus on discriminating between patients who are responsive or nonresponsive to pathological neoadjuvant chemotherapy . Few studies have examined radiomic features inside tumors for molecular subtype classification . Whether a regional analysis within the tumor could be more informative than an analysis of the entire tumor remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Present studies of intratumoral analyses mainly focus on discriminating between patients who are responsive or nonresponsive to pathological neoadjuvant chemotherapy . Few studies have examined radiomic features inside tumors for molecular subtype classification . Whether a regional analysis within the tumor could be more informative than an analysis of the entire tumor remains unclear.…”
mentioning
confidence: 99%
“…However, studies have suggested that intratumoral regions display distinct dynamic patterns, which reflect differing fundamental biological processes and differing prognostic potentials, 12 and could also possess valuable information that is not effectively captured by radiomic analysis of the entire tumor. [25][26][27] Present studies of intratumoral analyses mainly focus on discriminating between patients who are responsive or nonresponsive to pathological neoadjuvant chemotherapy. [27][28][29] Few studies have examined radiomic features inside tumors for molecular subtype classification.…”
mentioning
confidence: 99%
“…In addition, the following 5 semiquantitative metrics were quantified from the DCE-MRI signal time-course data, and voxel-based parametric maps were generated (41, 54, 55): Initial enhancement (WashIn) describes the initial signal increase from the precontrast value to the postcontrast value, as defined by the following equation: italicWashIn=smaxs0s0 where s 0 is the average of the precontrast baseline signal intensity and s max is the postcontrast signal intensity ~90 seconds after completion of CA injection.Signal enhancement ratio (SER) characterizes the postcontrast signal curve shape, as defined by the following equation: italicSER=smaxs0slasts0 where s last is the last signal value.After initial enhancement (WashOut), the signal curve behavior is described after the initial phase of contrast enhancement, as follows: italicWashOut=slastsmaxsitalicmaxWash-in slope (SlopeIn) is a measure of the CA uptake rate, and is calculated using the following equation: italicSlopeIn=smaxs0titalicmax where t max is the time when s max was measured.Area under the curve (AUC), the signal integral value, is defined using the following equation: italicAUC=truet0titaliclasts(t)dt where t 0 and t last are the first and last time points, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…174 DCE-MRI can be analyzed quantitatively by fitting the data to ad hoc or pharmacokinetic models that measure the time course of the presence of Cancer December 15, 2018 gadolinium within the tissues. 145,179,180 However, relevant to habitat imaging is that the lack of perfusion would be expected to correlate to hypoxia only in areas with relatively high cell density. 160,174 These parameters have been related to tumor angiogenesis and hypoxia by histological coregistration.…”
Section: Habitat Imagingmentioning
confidence: 99%